Metformin Alleviates Hepatic Steatosis and Insulin Resistance in a Mouse Model of High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease by Promoting Transcription Factor EB-Dependent Autophagy - Zhang, Dan; Ma, Yicheng; Liu, Jianjun; Deng, Yi; Zhou, Bo; Wen, Yu; Li, Mingke; Wen, Daiyan; Ying, Yunyan; Luo, Sufeng; Shi, Chunjing; Pu, Guangyu; et al. (Frontiers in Pharmacology, 2021)
Non-alcoholic fatty liver disease (NAFLD) results from the abnormal accumulation of lipids within hepatocytes, and commonly associated with obesity, insulin resistance, and hyperlipidemia. Metformin is commonly used to treat type 2 diabetes mellitus, in recent years, it was found to play a potential role in the amelioration of NAFLD. However, the mechanisms underlying the protective effect of metformin against NAFLD remain largely unknown. Transcription factor EB (TFEB) is a master transcriptional regulator of lysosomal biogenesis and autophagy, TFEB activation is effectively against the disorder of lipid metabolism. However, the role of TFEB in hepatic steatosis is not well understood. In this report, we demonstrate that TFEB activity is reduced in the liver of mice fed a high-fat diet. Metformin treatment significantly reverses the activity of TFEB, and the protective effect of metformin against hepatic steatosis and insulin resistance are dependent on TFEB. We also show that the activity of autophagy is regulated by TFEB, and our findings reveal that TFEB acts as a mediator linking metformin with autophagy to reverse NAFLD and highlight that TFEB may be a promising molecular target for the treatment of NAFLD.